An exceptionally stable Zr-based fluorescent metal–organic framework for highly selective detection of pH. Issue 1 (7th December 2018) - Wu, Shun-Hua; Wang, Shu; Fang, Wen-Le; Guo, Xiao-Feng; Wang, Hong
Abstract : UiO-67-bpydc was synthesized as pH sensor for specifically sensing pH in bodyfluids matrix, based on the protonation of bipyridine group. Abstract : In this study, we synthesized metal–organic frameworks (MOFs) UiO-67-bpydc using H2 bpydc as ligands and Zr6 clusters as vertexes. Due to the protonation of the bipyridine group, UiO-67-bpydc shows pH-dependent fluorescence (365 nm/530 nm) in the pH range from 1 to 9, which shows its feasibility as a wide-range pH sensor. Further study indicated that UiO-67-bpydc exhibits stability, reusability, selectivity and has an excellent linear relationship in the pH range 4.0–6.5, and the mechanism of the UiO-67-bpydc fluorescence intensity with the variation of pH has been studied in detail. This MOF-based fluorescent sensor has been applied to specifically detect the pH of solutions in the presence of the body fluid matrix. Compared with reported pH-MOF sensors, UiO-67-bpydc can be practically applied in real samples and is easily prepared with excellent stability in different buffer solutions.